Wear analysis of pin and roller surfaces. (March 2019) - El-Ghoul, Z; John, S; Dimkovski, Z; Lööf, P.-J; Lundmark, J; Mohlin, J
Abstract: In this paper three different combinations were evaluated: (i) steel pin vs steel roller, (ii) steel pin vs tungsten disulfide (WS2) coated roller and (iii) PVD pin vs steel roller. The aim of this paper is to properly quantify the topographical variations of the pin/roller surfaces and asses the appropriateness of the measuring technique before and after the tribological tests primarily performed for friction reduction. In-house tribometer was used to test the friction/wear performance of the three different combinations. Surface topographies were measured by white light interferometer (3D) and mechanical stylus (2D). To enable fast relocation on the stylus and interferometer, a 3D printed mask was used. Regarding the pins, Sa, Sk and Svk have been found to follow the wear changes: the lowest wear change for the combination (ii) and highest for the combination (i) but less for the combination (iii). Regarding the changes of Ra on the pin locations where edge contact occurs, the largest changes were found to be for combination (i), followed by combination (ii) and (iii). Ra and Rk change less significantly for the roller surfaces. Good correlations among the friction, initial/final roughness and radial displacements were also found.